The mechanistic role of alpha-synuclein in the nucleus: impaired nuclear function caused by familial Parkinson’s disease SNCA mutations - Chen, Vivian (Hum Mol Genet, 2020)
Alpha-synuclein SNCA has been implicated in the etiology of Parkinson’s disease (PD); however, the normal function of alpha-synuclein protein and the pathway that mediates its pathogenic effect is yet to be discovered. We investigated the mechanistic role of SNCA in the nucleus utilizing isogenic human-induced pluripotent stem cells-derived neurons from PD patients with autosomal dominant mutations, A53T and SNCA-triplication, and their corresponding corrected lines by genome- and epigenome-editing. Comparisons of shape and integrity of the nuclear envelope and its resistance to stresses found that both mutations result in similar nuclear envelope perturbations that were reversed in the isogenic mutation-corrected cells. Further mechanistic studies showed that SNCA mutation has adverse effects on the nucleus by trapping Ras-related nuclear protein (RAN) and preventing it from transporting key nuclear proteins such as, DNMT3A, for maintaining normal nuclear function. For the first time, we proposed that α-syn interacts with RAN and normally functions in the nucleocytoplasmic transport while exerts its pathogenic effect by sequestering RAN. We suggest that defects in the nucleocytoplasmic transport components may be a general pathomechanistic driver of neurodegenerative diseases.